DESIGN OF MARTAPURA RIVER BRIDGE STRUCTURE, BANJAR REGENCY - Markawie Markawie; Teguh Prastiyo; Ulfa Fitriati; Eddy nashrullah (Universitas Lambung Mangkurat, 2022)
The Martapura River Bridge is located on Jalan A. Yani KM 40 Martapura, Banjar Regency, South Kalimantan. Traffic processes that occur on Jalan A. Yani KM 40 Martapura often experience problems because congestion often occurs and the condition of the old IA bridge sometimes makes driving users feel restless when crossing the bridge located on the Martapura river. So that at the location of the Martapura river, it is deemed necessary to build a bridge next to the IA bridge so that the IB bridge to be built can be more sturdy and durable so that there is no anxiety for driving users and also to reduce congestion that occurs, where later the IB bridge will be used as a road with one way only towards Banjarmasin and the martapura IA bridge will be used as a one-way road towards the Hulu Sungai so that it will make it easier for traffic on Jalan A. Yani KM 40 Martapura. The methodology used in loading planning refers to SNI 1725-2016 concerning Loading Standards for Bridges. For the methodology in calculating the stress loss, refer to the NAASRA Bridge Design Specification on Chapter VI Bridge Design Specifications (Prestressed Concrete Design). For the methodology in calculating the moment of the vehicle floor using the Three Moment Equation method and for the method of subsidence of group pile foundations using the method of Schultze and Sheriff (1973), assuming that the pile group is the Equivalent Raft Foundation. The material used in the design of the upper structure is prestressed concrete, while the lower structure is planned to use reinforced concrete with a square pile. The results obtained are the T-Girder Prestressed type bridge with class A, 34 m span, 7 m traffic width, and 1 m wide sidewalk. Prestressed T-Girder is designed using fc' 40 MPa (K-482) Strands used are uncoated 7 wire super strands ASTM A-416 grade 270 with a diameter of 12.7 mm and an area of 100 mm2 with a tensile strength of 1860 MPa. As for the lower structure, the abutment uses concrete with a quality of fc' 25 MPa (K-300) with a height of 565 cm, a width of 480 cm and a length of 1050 cm.type piles Square Pile with a length of 15 m with a quality of 50 MPa (K-600) with a width of 60x60 cm with a configuration of 18 piles for each abutment. Estimated Budget Plan The cost of constructing the Martapura river bridge is IDR 8,129.511,475.00.-.